Peran Media Planner, Content Planner, dan Copywriter dalam Brand Communication “Bercerita Di Bu Lurah” sebagai Upaya Penguatan Brand Image Kopi Susu Bu Lurah Semarang - Agatha Nuansa Natnesia Daniswara; Lintang Ratri Rahmiaji (Interaksi Online, 2026)
This study aims to analyze the effectiveness of the “Bercerita di Bu Lurah” campaign in strengthening the brand image of Kopi Susu Bu Lurah through the roles of Media Planner, Content Planner, and Copywriter. The research employs a qualitative descriptive approach supported by quantitative data using a pretest posttest method with 300 respondents. The campaign integrates online and offline activities, including the “Ditraktir Bu Lurah” program and human connection based social media content. Survey findings reveal a shift in audience perception, from viewing the brand as a regular coffee shop to recognizing it as a warm and inclusive social space